Simplifique as expressões algébricas abaixo reduzindo os termos semelhantes:
a) 3a + 7b - 4c + 5a + 4b + 8c =
b) 2( 3m + 4n) + 5m - 3n =
Soluções para a tarefa
Respondido por
0
Resposta:
A) 8a 11b 4c
B) 11m 5n
Explicação passo-a-passo:
A)
3a + 7b - 4c + 5a + 4b + 8c
3a+5a=8a
7b+4b=11b
-4c+8c=4c
B)
2( 3m + 4n) + 5m - 3n =
2.3m+2.4n+5m-3n
6m+8n+5m-3n
6m+5m=11m
8n-3n=5n
Perguntas interessantes
História,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
9 meses atrás
Português,
9 meses atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás